A new perspective on the nail plate for treatment of ingrown toenail - Jia Tian; Jin Li; Fabin Wang; Zhenbingi Chen (Mattioli1885, 2018)
Background: Our routine treatment for ingrown toenail was removal of the surrounding soft tissue and shortening the bone of the distal phalanx. We determined the range and volume of excision based on our experience without an objective standard and routinely performed avulsion of the nail plate. Objective: To take the nail plate as an objective mark during surgical treatment of ingrown toenail to ensure accurate excision. Patients and Methods: Fifteen patients with ingrown toenails were treated with this technique. We used the lateral borders of the nail plate as a landmark to determine the volume of soft tissue surrounding the nail plate and distal phalanx to be removed. No avulsion of nail plate was performed. Results: No recurrence was observed during the follow-up period, which ranged from 24 to 35 months (29.9 months on average). The visual analog scale for pain showed significant pain relief in the patients. The Vancouver Scar Scale showed acceptable cosmetic outcomes. The width of excised skin ranged from 3.5 to 6.2 mm (5.0 mm on average). Conclusion: The use of the lateral borders of the nail plate as a landmark for surgical intervention of ingrown toenail offered excellent outcomes and reduced loss of healthy tissues.